Older Adults and Covid‐19: The Most Vulnerable, the Hardest Hit. Issue 3 (29th June 2020) - Powell, Tia; Bellin, Eran; Ehrlich, Amy R.
Abstract: Older adults in the United States have been the age group hardest hit by the Covid pandemic. They have suffered a disproportionate number of deaths; Covid patients eighty years or older on ventilators had fatality rates higher than 90 percent. How could we have better protected older adults? Both the popular press and government entities blamed nursing homes, labeling them "snake pits" and imposing harsh fines and arduous new regulations. We argue that this approach is unlikely to improve protections for older adults. Rather than focusing exclusively on acute and critical resources, including ventilators, a plan that respected the best interests of older adults would have also supported nursing homes, a critical part of the health care system. Better access to protective equipment for staff members, early testing of staff members and patients, and enhanced means of communication with families were what was needed. These preventive measures would have offered greater benefit to the oldest members of our population than the exclusive focus on acute care .